Impact of Sky View Factor on Outdoor Thermal Comfort - Solanki, Pooja; Amirtham, Lilly Rose (Calibrating Urban Livability in the Global South, 2024)
Cities are vulnerable to temperature changes due to the inappropriate urbanization process causing Urban Heat Island effect, which exacerbates the instability of the thermal environment and the risk of human heat exposure. The 2021 IPCC Sixth Assessment Report indicates a 1.09°C rise in global average temperature from 2011 to 2020, along with increased frequency and intensity of extreme heat events. Higher Sky View Factors (SVFs) amplify the reflections of short-wave and long-wave radiations, creating uncomfortable outdoor thermal environment, crucial in Urban Morphology and Climatology. Therefore, this research aims to examine the effect of SVF on Thermal Comfort in a warm-humid Climate of India. Varying ranges of SVFs in residential neighbourhoods (0.868, 0.807, 0.693, 0.648, 0.523 and 0.372) were selected for this study as per the local bye-laws and its impact on thermal comfort were analyzed using RayMan Tool and ENVI-met software. The study found least R2 value for SVF of 0.868, followed by SVF of 0.807 with R2 of 0.63, and SVFs of 0.693, 0.648, 0.523 and 0.372 were statistically significant. Amongst all the selected SVFs, the SVF of 0.523 has the most significant corelation with R2 of 0.953. The results show that SVF ranged between 0.693 and 0.372 had a strong impact on PET (Physiologically Equivalent Temperature) and MRT (mean radiant temperature) values highlighting the significance of SVF in determining comfort conditions. This results of this research can aid architects and planners in creating a climate-resilient design by optimizing urban morphology in enhancing thermal comfort in cities.